Tantangan Sistem Ekonomi Islam Di Era Industri 4.0 Dalam Mendukung Pertumbuhan Ekonomi Di Indonesia - nissa, izzun khoirun; Sulistyowati; Asti Marlina; Jessica Allya Putri; Chusnul Intan Alfiana (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2024)
The development of the times is something that is common and will continue to occur along with increasing knowledge and the desire to be more advanced and facilitate human activities. In the current era of digitalization, some Muslims can understand the probability of changing industry 4.0 by using digital technology as a means of collecting sustenance. . Islamic economics is present as a means of meeting the economic needs of Muslims, in which this economic system has been taught by the Prophet and his companions in the process of life. Islamic economics can also be expressed in terms of Islamic economics. Both have the same meaning that both are based on Islamic teachings. In the research on the Challenges of the Islamic Economic System in the Industrial Age 4.0 in Supporting Economic Growth in Indonesia, the design of this study only focuses on important points that can be extracted from existing sources, so that the research is based on Descriptive Analysis techniques, namely a type of research data that assists in describing, demonstrating, or assisting in summarizing data points so that patterns can develop that satisfy all data conditions. The author discusses this theme because we feel the need to understand the Syari'ah economic system as a Muslim economic vessel.